Pengaruh konflik peranan terhadap hasrat persaraan awal pemimpin guru: kepuasan kerja sebagai mediator - Norhana, Mohamad Saad (2020)
The Ministry of Education Malaysia is committed to ensuring that teachers serve until the end of their service. However, there is an increase in the desire for early retirement among teachers. Job satisfaction resulting from the resolution of role conflicts is seen to encourage early retirement. Therefore, a detailed study was done to examine the cause of the problem. This study examined the level of role conflict (KP), job satisfaction (KK) and early retirement intentions (HPA) based on gender and age, the relationship between KP, KK and HPA; as well as determining whether KK as a mediator affects the relationship between KP and HPA. Other contributing factors were also studied. Quantitative data using questionnaires that have been completed by 347 secondary school teacher leaders in the state of Kelantan were analyzed using descriptive and inferential statistics. While the qualitative data obtained through interviews with seven teacher leaders were analyzed thematically. The findings of the study indicated that the role conflict (M=4.06, SD=.44) and early retirement intentions (M=4.19, SD=.41) were at a high level while job satisfaction (M=3.89, SD=.42) of teacher leaders was at a moderate level. The findings showed that there was no significant difference in the level of role conflict, job satisfaction and early retirement intentions among teacher leaders based on gender and age. There was a significant positive relationship between role conflict, job satisfaction and early retirement aspirations; role conflict and job satisfaction has a significant positive influence on early retirement intentions. In addition, the findings of this study indicated that job satisfaction played a role as an important mediator between role conflict and early retirement intentions. Qualitative findings analysis found other contributing factors were lack of information technology skills, health problems, financially stable, wanting family time, filling time meaningfully and venturing into other fields. The findings of this study contributed to the development of the theory of role conflict, job satisfaction and early retirement intentions. To reduce the desire for early retirement, this study suggested that job satisfaction, role conflict and other factors as contributors should be given attention by relevant parties.